2018
DOI: 10.1097/bot.0000000000001079
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Radiographic Outcomes After Allograft Anatomic Coracoclavicular Ligament Reconstruction

Abstract: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…Other authors reported no clavicle fractures with use of similar reconstruction constructs. Baran et al 19) evaluated outcomes of 17 patients after CC reconstructions with hamstring allografts. Tendon was passed under the coracoid and fixed over the clavicle through double tunnels, unlikely in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors reported no clavicle fractures with use of similar reconstruction constructs. Baran et al 19) evaluated outcomes of 17 patients after CC reconstructions with hamstring allografts. Tendon was passed under the coracoid and fixed over the clavicle through double tunnels, unlikely in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Although, allografts and autografts such as palmaris longus, 60,82 flexor carpi radialis, 82 peroneus longus, 83 and tibialis anterior tendons 84 have been utilized for the treatment of AC joint dislocations, hamstring tendons are most commonly used. 53,64,77,[84][85][86][87] Tendon grafts are used in both acute and chronic AC joint dislocations, however, they are most beneficial in chronic AC joint injuries, since in order to facilitate healing, biological augmentation is needed. 88 Free tendon grafts have been shown to provide superior biomechanical strength compared to the Weaver-Dunn procedure 65,82,87,89 and similar biomechanical strength to suspensory button devices.…”
Section: Reconstruction With Allo-and Autograftsmentioning
confidence: 99%
“…Several biomechanical studies have demonstrated that large tunnels are associated with an increased fracture risk and with reduced load to failure [ 6 , 7 , 10 , 26 ]. Furthermore, in several studies, progressive tunnel widening was observed during the postoperative course, with differing results regarding loss of reduction [ 1 , 2 , 9 , 16 , 23 , 25 , 28 ]. Influencing factors might be the material and type of AC repair device and associated micro-motions between the bone and suture material as well as heat-induced osteolysis due to the bone drilling.…”
Section: Introductionmentioning
confidence: 99%